2017
DOI: 10.1016/j.ejca.2017.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Five years of EMA-approved systemic cancer therapies for solid tumours—a comparison of two thresholds for meaningful clinical benefit

Abstract: In most of the cancer drugs, the MCB threshold is not met at the time of approval when measured using both ESMO-MCBS scales. Since approval status does not translate into a MCB, stakeholders and decision makers should focus on the benefit/risk ratio of anticancer drugs to assure an appropriate allocation of resources in health care systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 22 publications
4
29
0
3
Order By: Relevance
“…However, whereas the academic trials included a range of nondrug interventions, with more than half (58%) in the curative setting, the industry-sponsored trials were weighted heavily (79%) toward drug trials in the noncurative setting. This preponderance of trials in noncurative settings is supported in other studies [8,18,19].…”
Section: Clinical Benefitssupporting
confidence: 69%
See 1 more Smart Citation
“…However, whereas the academic trials included a range of nondrug interventions, with more than half (58%) in the curative setting, the industry-sponsored trials were weighted heavily (79%) toward drug trials in the noncurative setting. This preponderance of trials in noncurative settings is supported in other studies [8,18,19].…”
Section: Clinical Benefitssupporting
confidence: 69%
“…The European Society for Medical Oncology Magnitude of Clinical Benefit Scale (ESMO-MCBS) is a tool used to assess the clinical benefit of novel cancer therapies [10] and has been reported to correlate with clinically relevant survival gains [11]. Using both the ESMO-MCBS and a modified version adapted for Health Technology Assessment (HTA) [12], an analysis of 5 years (2011-2016) of EMA cancer drug approvals showed that 89 and 79% of therapies did not meet the MCBS or modified threshold respectively [13]. A USA analysis, using the ESMO-MCBS threshold, showed that over the period of 2006-2016, only 43.8% of randomized controlled trials supporting FDA approvals for new cancer drugs met the MCB threshold [14].…”
Section: Clinical Benefitsmentioning
confidence: 99%
“…Se usan cuando los desenlaces críticos e importantes son raros o se presentan a largo plazo (5,39). Otras razones para usar estos desenlaces son: 1) las terapias que reciben los pacientes antes y después de los estudios, lo que dificulta evaluar el efecto clínico de la intervención; 2) la posible alteración de la SG al cruzar los pacientes a nuevas terapias luego de las investigaciones, cuando se encuentra una adecuada eficacia de estas (21); 3) la historia natural de algunos Ca muestra una SG larga, explicada por efecto del diagnóstico y el tratamiento tempranos, lo que obligaría a realizar investigaciones de larga duración con muestras grandes, lo que dificulta su realización (39) y; 4) el uso de desenlaces sustitutos, acorta la duración de las investigaciones y el tiempo de aprobación de los medicamentos (7,14).…”
Section: ¿Por Qué Se Usan Los Desenlaces Sub-ro-gados En Los Estudiosunclassified
“…Los tratamientos anti-Ca tienen un alto costo, situación que viola los principios éticos, justicia y equidad; al promover terapias con pocos beneficios clínicos, se pueden negar recursos que permitan implementar en forma temprana estrategias diagnósticas y de intervención para las neoplasias malignas (7,13,14).…”
Section: ¿Existe Lucro Por La Aprobación De Medi-camentos Anti-cáncer?unclassified
See 1 more Smart Citation